Linear-stapled side-to-side esophagojejunostomy with hand-sewn closure of the common enterotomy after prophylactic and therapeutic total gastrectomy - Chang, Kevin K. (J Gastrointest Surg, 2016)
After total gastrectomy, anastomosis-related complications such as leak or stricture can be highly morbid. Between July 2005 and December 2015, a linear-stapled side-to-side esophagojejunostomy with hand-sewn closure of the common enterotomy (modified Orringer technique) was used for Roux-en-Y reconstruction after prophylactic total gastrectomy in 22 germline CDH1 mutation carriers and after therapeutic total gastrectomy in 18 patients diagnosed with gastric adenocarcinoma. All operations were performed by the same surgeon. No patient in either cohort developed a clinically evident anastomotic leak, one patient (2.5%) developed a contained radiographic leak that healed without intervention, and one patient (2.5%) developed an anastomotic stricture treated by endoscopic dilatation 7 months after operation. These rates were lower than radiographic leak and stricture rates in a comparison group of 32 patients who received a completely hand-sewn esophagojejunostomy (6.3% and 3.1%, respectively). Here we describe how to perform the linear-stapled esophagojejunostomy anastomosis.